Análisis de la situación financiera de las Pymes del Sector de Autopartes en la ciudad de Barranquilla durante los años 2013, 2014 Y 2015, en comparación con el año 2018 (2019)
This project and research shows an analysis of the financial situation of small and medium-sized companies in the auto parts sector in the city of Barranquilla during the years 2013, 2014 and 2015, comparing the results with the year 2018. The above, taking into account that this type of companies contribute to the economic development of the country, and especially of the region, and also counting on the great boom of the Autoparts sector, which has consolidated in the country over the last years thanks to the implementation of free treaties trade and import strategies. Through the use of financial tools, it is intended to make a diagnosis that determines the financial status of the small and medium-sized companies in the sector and, using their basic financial statements, it is intended to fulfill the initial purpose. The four main areas of this group of companies are then analyzed: liquidity, turnover, indebtedness and profitability.